2018
DOI: 10.1021/acs.analchem.8b00537
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Pesticides by Gas Chromatography Combined with Mass Spectrometry Using Femtosecond Lasers Emitting at 267, 400, and 800 nm as the Ionization Source

Abstract: A standard sample mixture containing 51 pesticides was separated by gas chromatography (GC), and the constituents were identified by mass spectrometry (MS) using femtosecond lasers emitting at 267, 400, and 800 nm as the ionization source. A two-dimensional display of the GC/MS was successfully used for the determination of these compounds. A molecular ion was observed for 38 of the compounds at 267 nm and for 30 of the compounds at 800 nm, in contrast to 27 among 50 compounds when electron ionization was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…It has been reported that a bulky side chain, i.e., a low frequency mode in a molecule accelerate fragmentation. 24 As can be seen from the chemical formula of DDT (Fig. S-1), it contains two bulky groups and HCB has a rigid Please do not adjust margins Please do not adjust margins structure, which explains the more dissociative nature of DDT compared to HCB.…”
Section: Re2pimentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that a bulky side chain, i.e., a low frequency mode in a molecule accelerate fragmentation. 24 As can be seen from the chemical formula of DDT (Fig. S-1), it contains two bulky groups and HCB has a rigid Please do not adjust margins Please do not adjust margins structure, which explains the more dissociative nature of DDT compared to HCB.…”
Section: Re2pimentioning
confidence: 99%
“…23 This technique has been applied for the measurement of analytically important compounds, e.g., chlorinated aliphatic/aromatic hydrocarbons such as OCPs. 24 However, the mechanism responsible for this ionization has not yet been investigated to date.…”
Section: Introductionmentioning
confidence: 99%
“…1518 MPI-TOFMS is normally applied to atomic/molecular spectroscopy 1921 and to the trace analysis of compounds in real samples such as in an environmental setting. 2227 Although MPI is generally an ionization method for analytes in a gas phase, several vaporization methods for liquid samples have also been studied. 2830…”
Section: Introductionmentioning
confidence: 99%
“…If the pesticides applied on soils, it persists for a long time, because its degradation is slow and it is harmful to the human being [2][3][4][5], therefore, there is necessary to monitoring of pesticides. Many monitoring techniques have been reported for the quantitative determination of pesticides such as spectrophotometry, capillary electrophoresis, highperformance liquid chromatography (HPLC), liquid chromatography-mass spectrometry (LC-MS), and ultraperformance liquid chromatography coupled to tandem mass spectrometry [6][7][8][9][10][11][12][13][14][15]. Thus, electrochemical methods offer a versatile stand for sensitive, selective and reproducible evaluating of pesticides.…”
Section: Introductionmentioning
confidence: 99%